The Factors Affecting Savings Volume in Lao PDR - MINGBOUPPHA , Khonesavanh; HER, Pheng; VATTHANA, Mongkhoun (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This study aims to analyze the economic factors influencing the level of savings in the Lao People's Democratic Republic (Lao PDR) using time series data from 2000 to 2023. The key variables examined include Official Development Assistance (ODA), Gross Domestic Product (GDP) per capita, inflation rate, and interest rate. These variables have not been specifically applied to the context of Lao PDR in previous studies. The analysis employs descriptive statistics, the Ordinary Least Squares (OLS) method, and an error correction model. Findings indicate that economic factors significantly impacted savings in Lao PDR over the 23-year period. During this time, the country experienced increased foreign aid and investment, as well as growth in exports, leading to a steady rise in GDP per capita—from 0.77% in 2000 to 10.60% in 2023. Correspondingly, the domestic savings rate increased from 0.56% to 12.78%. The regression analysis reveals that a 1% increase in ODA leads to a 0.5242% rise in domestic savings. Similarly, a 1% increase in GDP per capita, inflation rate, and interest rate results in increases in domestic savings by 0.2460%, 0.3146%, and 0.1842%, respectively. All results are statistically significant at the 1% level.